The Philosophical Roots of the Marx-Bakunin Conflict - Robertson, Ann (Hybris, 2018)
This essay explores the underlying philosophical differences separating Marxism and anarchism by examining the specific philosophies of Marx and Bakunin. The conflicting philosophical foundations of these two philosophers reveal why there were irreconcilable political and strategic differences between them, even though both were members of the First International and both were equally dedicated to the abolition of capitalism. Bakunin, for example, posited humans as basically natural creatures with permanently fixed natures while for Marx humans have been evolving throughout history, becoming more rational in the process, and thus exhibiting different human natures in different historical periods. Accordingly, both authors adopted starkly different conceptions of freedom, where Bakunin sought to identify freedom with acting according to natural impulses while Marx defined it in terms of conscious, rational collective action. With these contrasting philosophical foundations Marx and Bakunin proceeded to outline incompatible theories of the State and diverging strategies in abolishing it; they disagreed on who would be most likely to lead a revolutionary upheaval; and they differed on what organizational forms would be needed to accomplish their revolutionary aims.